The haematological influences of seaweed extract on growing japanese quails - Ercan Keskin; Zafer Durgun; Mehmet Kocabatmaz (Eurasian Journal of Veterinary Sciences)
In this study we attemted to investigate the effect of seaweed extract (Maxicrop) added at different levels to rations of growing quail chicks. Eighty, one day old Japanese quail chicks were used in this experiment They were randomly distributed in four groups, each including 20 chicks. The chicks in group l(control), II, III and IV were fed control ration, the ration containing 1, 0,1 and 0.01 % seaweed extract, respectively until they reached 5 weeks of age. The animals were offered the rations and the water ad iibitum. At 1 st. 2 nd and 3 rd weeks of age. 5 chicks of each group were randomly slaughtered for blood withdrawal from each chicks. At the and of the first week, the erythrocyte count, hemoglobine amount, haematocrit value, plasma glucose and total protein levels in group II ted ration caontaining %1 seaweed extract were found higher than other groups altough it was no differences among all groups (P>0.05). At the termination of the fifth week, erythocyte count, hemoglobine amount and haemotocrit value in group ll were determined signifacantly higher than group I and IV (P<0.05). At that time the plasma glucose and total protein levels were found obviously higher in group II as compared to other groups and plasma glucose level in group II was significantly different than group I and IV (P<0.05) During the whole experiment, it was not dtermined striking changes in respect to leucocyte types, leucocyte and trombocyte counts in all groups.